Moral Injury, Betrayal and Retribution: Australian Veterans and the Role of Chaplains - Hodgson, Timothy J. (Journal of religion and health, 2022)
This paper presents additional qualitative results from Phase 1 of a larger study examining potentially morally injurious events/experiences (PMIE) and/or moral injury (MI) among Australian veterans (Hodgson et al. in J Relig Health 60(5):3061-3089, 2021). It makes specific reference to (1) betrayal and (2) retribution experienced or perpetrated by Australian military veterans during military conflicts and peacekeeping missions. During two veteran seminars conducted in Adelaide, South Australia, a total of 50 veterans were recruited, 10 of whom were willing to be interviewed and audio-recorded about their deployment experiences. Narrative data analysis of veteran transcripts indicated that all participants had engaged in or were exposed to a PMIE/MI of one kind or another, and all had experienced betrayal and/or witnessed or perpetrated retribution. Given the ethical, moral and spiritual issues involved, the role of chaplains in addressing moral injury for the benefit of veterans through the use of ‘Pastoral Narrative Disclosure’ (PND) is suggested—with a specific focus upon ‘restoration’ and ‘ritual’. Additional research is recommended with regard to acts of betrayal and retribution among veterans, as well as the further development of PND to address PMIE/MI.